Characteristics of the treatment process among patients with hip fractures against the background of COVID-19 - S.O. Guriev; E.O. Skobenko (Bolʹ, Sustavy, Pozvonočnik)
Background. Already from the beginning of the COVID-19 epidemic, both in Ukraine and in the world, there was a problem of providing trauma care to victims with traumatic injuries, which was combined with similar problems with medical care for other categories of patients. The system of routing patients with hip fractures against the background of COVID-19 during the epidemic period, depending on the severity of the course, will allow to organize a system of providing medical care to such patients, which will correspond to both the personnel and material resources necessary to overcome the consequences of this pandemic. The aim of our study was to analyze the distribution of patients with femur fractures during the COVID-19 epidemic and to determine changes in approaches to their treatment. Materials and methods. To conduct our study, we retrospectively analyzed the treatment of 289 trauma patients who underwent inpatient treatment in 2019–2021. Results. The number of surgical interventions in patients with hip fractures decreased by only 2.8 %, which indicates the absence of changes in the tactics of treatment of patients with this pathology during the epidemic period. There were no changes in the number of patients with diaphyseal femur fractures; their number was constant in both research periods. However, during the epidemic period, an increase in the level of surgical interventions in patients with fractures of the diaphyseal part of the femur was found. During the COVID-19 epidemic, there was a decrease in the number of victims with fractures in the distal part of the hip. During the epidemic period, the rate of distal hip fractures decreased by 6.0 %. An increase in operative activity was found in relation to patients with fractures of the distal part of the femur in the pre-operative period. Conclusions. In the period of COVID-19, the number of patients with hip fractures increased, and no changes in the structure of treatment of patients in this category were found. During the COVID-19 epidemic, there were no changes in the number of patients with diaphyseal hip fractures, their number was constant in both research periods. However, during the epidemic period, an increase in the level of surgical interventions in patients with fractures of the diaphyseal part of the femur was found. During the epidemic period, there was a decrease in the level of victims with fractures in the distal part of the thigh by 6.0 %, and an increase in operative activity was detected in relation to patients from this category.